Wewenang Notaris Membuat Surat Kuasa Membebankan Hak Tanggungan (SKMHT) Menggunakan Blanko Yang Disediakan Oleh Badan Pertanahan Republik Indonesia - Ni Made Arnita Sari; I Nyoman Sumardika; Ni Made Puspasutari Ujianti (Jurnal Analogi Hukum, 2021)
A notary is a public official who is authorized to make authentic deeds, and one of his authorities is to make a Power of Attorney to Charge Mortgage Rights hereinafter referred to as SKMHT. The authority of a notary to be able to make SKMHT can be done by making his own notary deed that has been prepared by a notary issued by National Land Agency of the Republic of Indonesia. A notary is a public official whose sole authority is to make an authentic deed regarding all acts, agreements and stipulations required by a general regulation or by an interest desired to be stated in an authentic deed. The formulations of the problems used are: 1. Is the power of attorney to impose mortgage rights (SKMHT) made by a Notary using the form provided by the National Land Agency of the Republic of Indonesia is not an authentic deed? 2. What are the legal consequences if the power of attorney to impose mortgage rights (SKMHT) made by a notary using the form provided by the National Land Agency of the Republic of Indonesia? The research method used in this study is a type of normative legal research. The approach adopted to discuss the problems in this study is through the statute approach and the conceptual approach. So the Notary is authorized to make SKMHT as stipulated in Article 15 paragraph (1) UUHT, but if the SKMHT he uses the SKHMT form provided by the Republic of Indonesia BPN, then the SKHMT he made does not fulfill the provisions of Article 38 UUJN, so the SKMHT Deed he made is not Authentic Deed, but only in the form of Deed Under the Hand. As a result of the law if the SKMHT made by the Notary uses the SKHMT form provided by the Republic of Indonesia BPN, it will result in a Notary, SKMHT made by a Notary null and void